An Empirical Study of Sectoral-Level Investments in New Zealand - Razzak, W. A. (Journal of Reviews on Global Economics, 2014)
We extend the Glick and Rogoff (1995) aggregate time-series, empirical, intertemporal model of country-investment to a sectoral-level, and estimate it for New Zealand. We fit the model to panel data of eleven industries from 1988-2009. The sectoral-level investment growth is a function of lagged investment level, sector-specific total factor productivity shocks (TFP), country-specific TFP shocks, and global TFP shocks. The estimates seem robust to government spending shocks and Terms of Trade shocks.